Overlooking the Obvious during the COVID-19 Pandemic: Dyspnoea with Asymmetric Breath Sounds in a Toddler - Heli Salmi; Heini Harve-Rytsälä; Paula Rautiainen; Sari Pyörälä; Johanna Hästbacka (Case Reports in Pediatrics)
Background. Paediatric healthcare specialists are concerned about the secondary effects of the COVID-19 pandemic on children. We report a case of acute respiratory distress in a healthy toddler whose healthcare providers were sidetracked from the correct diagnosis by suspicion of COVID-19. Case Presentation. The patient was a 20-month-old healthy boy. In the morning, he had coughed while drinking milk. He was asymptomatic for the day but presented with acute respiratory distress when lying down in the evening. An ambulance was called, and he was taken to a tertiary hospital’s paediatric emergency department, where his condition and oxygen saturation fluctuated. He had mildly elevated temperature and petechiae on his trunk, showed asymmetrical radiographic and auscultatory pulmonary findings, and did not tolerate any exertion. Pneumonia was suspected, SARS-CoV-2 was considered as potential causative agent, and the child was admitted to a Paediatric Intensive Care Unit. As the patient did not show clear signs of infection or bronchial obstruction, the events were thoroughly rediscussed with the caregiver next morning. It was then found out that the child had also been eating cashew nuts. Multiple pieces of cashew nuts were removed from the left bronchial tree in a bronchoscopy. After the procedure, all symptoms promptly resolved. Foreign body aspiration—an obvious cause of acute respiratory distress in our patient’s age group—was overlooked by experienced emergency medical care providers and paediatric critical care physicians due to the slightly unusual presentation, incomplete anamnestic information, and a bias to consider COVID-19 in the current exceptional circumstances. Conclusions. Emergency care providers are instructed to consider all patients with respiratory distress as potential COVID-19 patients. However, the clinical course of COVID-19 infection is usually mild in children. Therefore, alternative causes for serious breathing difficulty are more likely, and all differential diagnoses should be considered in the usual unbiased manner.